Surgical treatment of brain tumors without informed consent - medical, organizational and legal aspect - Siedlecki, Zygmunt; Gutkowska, Agnieszka; Śniegocki, Maciej (Journal of Education, Health and Sport, 2020)
Brain tumors are often manifested by mental disorders. Changes in personality, behavior and logical functions are often the dominant pathological symptoms in patients with brain tumors. There are also cases where brain tumors occur in patients with psychotic disorders or mental retardation and in these particular cases, they aggravate the already advanced mental disability. As a result, patients with brain tumors are often intellectually disabled and it is not possible to perform informed consent to treatment. In clinical practice, those patients who require neurosurgical treatment must give their informed consent, and when it is not possible, the judicial consent must be adjudicated. In urgent cases, medical decision on surgery is necessary in algorithm of life saving surgery, due to size of tumor and brain edema. We present the current state of knowledge and the facts about neurosurgical prcedures performed in patients with brain tumors without obtaining informed consent. We analyze the medical, legal and organizational status, pay attention to the nuances and the need for outstanding clinical experience in such a delicate matter. Clinical experience and legal awareness is essential for a qualifying neurosurgeon.